Control of cacao (Theobroma cacao) diseases in Santo Domingo de los Tsachilas, Ecuador - Anzules-Toala, Vicente; Pazmiño-Bonilla, Elvis; Alvarado-Huamán, Leonel; Borjas-Ventura, Ricardo; Castro-Cepero, Viviana; Julca-Otiniano, Alberto (Agronomía Mesoamericana, 2021)
Introduction. Ecuador occupies the fourth place in cocoa exports with 293,487 tons per year, produced on 559,617 hectares. However, its yield per hectare is low mainly due to the presence of pathogens that affect the pods. Objective. To evaluates different methods of control of pathogens of the Theobroma cacao cv ‘CCN-51’ pod. Materials and methods. The work was carried out in Luz de America, Santo Domingo de los Tsachilas, Ecuador, between 2016 and 2017. The treatments were the result of the combination of cultural practices + two fungicides (Chlorothalonil and Pyraclostrobin) + one biofungicide Serenade® (Bacillus subtilis QST713), with and without fertilizers. In total, 16 treatments were evaluated with 3 replicates or blocks, installed in a commercial cocoa plantation cv ‘CCN-51’ and under a Randomized Complete Block Design (RCBD). Results. The use of fungicides (chemical and biological), decreased the incidence of moniliasis (Moniliophthora roreri), black pod rot (Phytophthora spp.), and cherelle wilt; but the application of fertilizers did not increase the effectiveness of these products. Treatment with only cultural practices did not decrease the final incidence of moniliasis, nor of brown rot, in contrast, the final incidence of cherelle wilt increased. The number of pods and the yield were not directly related and the highest yield of fermented and dry cocoa, corresponded to T9 [Cultural labors + Serenade® (0.2 kg ha-1) (every 15 days) + Fertilizer (0.3 kg ha-1) + Fertilizer (1 kg plant-1)], a treatment that also had the highest net income per hectare. Conclusion. Chemical and biological control can manage cocoa pods pathogens. The integration of both control methods allowed the cocoa producer to obtain greater income.